Social issues in contemporary native America [ reflections from Turtle Island - Weaver, Hilary N. (Ashgate Publishing, 2014)
"Hilary Weaver has drawn together leading Native American social workers, researchers, and academics to provide current information on a variety of social issues related to Native American children, families, and reservations both in the USA and in Canada. Divided into four major sections, each containing an introduction, this book places the historical foundations of Native American social work in context in order to fully provide the reader with a comprehensive survey on various aspects of working with Native American families; community health and wellness; and community revitalization and decolonization. This groundbreaking volume should be read by both educators and students in social work and other helping professions in the USA and Canada as well as all human service professionals working with Native Americans."